2002
DOI: 10.1046/j.1540-8175.2002.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Accessory Atrioventricular Pathways by Doppler Myocardial Imaging

Abstract: Our findings demonstrate the feasibility of DMI to assess the early ventricular contraction associated with atrioventricular accessory pathways. Therefore, DMI appears to be a clinically useful adjunct to noninvasive evaluation of abnormal myocardial depolarization in WPW and to evaluate the results after radiofrequency ablation, even though its accuracy is considerably better for left-sided accessory pathways than for right-sided ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…Other methods that have been employed to detect the AP include M-mode echocardiography, phase analysis of 2-dimensional echocardiographic images, Doppler myocardial imaging, and TDI. [10][11][12][13][14][15][16][17] These methods have focused mainly on abnormal ventricular motion. Previous authors have, for example, analyzed the time-sequential changes in ventricular wall motion in WPW syndrome using TDI in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods that have been employed to detect the AP include M-mode echocardiography, phase analysis of 2-dimensional echocardiographic images, Doppler myocardial imaging, and TDI. [10][11][12][13][14][15][16][17] These methods have focused mainly on abnormal ventricular motion. Previous authors have, for example, analyzed the time-sequential changes in ventricular wall motion in WPW syndrome using TDI in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Different TDI modalities with M-mode Doppler, velocity mode, acceleration mode and pulsedwave Doppler have used for the detection of the accessory pathways in several studies [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent applications of TDI are in the evaluation of regional left ventricular (LV) systolic and diastolic functions [2][3][4][5]. Also, TDI offers the promise for the detection of the earliest ventricular contraction site and the time-squential changes in myocardial depolarization [6][7][8][9][10][11]. Several studies reported the ability of the color-coded TDI (velocity or acceleration map) or pulsed-wave TDI modalities to localize the site of the accessory atrioventricular pathways and to evaluate the results of radiofrequency ablation [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delta wave polarity or QRS polarity on a 12 lead ECG has been widely used to determine accessory pathway location. [1][2][3][4][5] Related to echocardiography, M-mode echocardiography, [6][7][8] phase analysis of echocardiographic images, 9,10) Doppler tissue imaging, 11,12) and Doppler myocardial imaging 13) have also been employed to detect the accessory pathway side. These methods have focused mainly on abnormal ventricular motion.…”
mentioning
confidence: 99%